Evaluation of LLDPE/LDPE blend foamability by in situ rheological measurements and bubble growth simulations. (31st December 2018) - Chen, Yichong; Wan, Chen; Liu, Tao; Chen, Zheqi; Qiao, Yida; Lu, Jiawei; Yan, Junyu; Zhao, Ling; Esseghir, Mohamed
Graphical abstract: Highlights: The LLDPE/LDPE blends' rheological properties were measured under compressed CO2 . The foamability was simulated by the bubble growth and stability models. The LLDPE/LDPE blends with mass ratio of 5/95 possessed the best foamability. Abstract: Polyethylene (PE) foams, which constitute a large share of the total production of thermoplastic foams worldwide, are mainly derived from low density PE (LDPE). In this study, linear low-density PE (LLDPE), with its good mechanical properties but inferior foamability, was blended with LDPE by twin-screw compounding at varying mass ratios of 0/100, 5/95, 15/85, 25/75, and 100/0. Differential scanning calorimetry and small amplitude oscillation shear tests confirmed the compatibility of the blends. A high-pressure rheometer was used to measure the rheological properties of the blends under different CO2 pressures with the aid of a homemade fixture. Gotsis' model was applied to correlate the rheological data for the blends and obtain their characteristic relaxation time and rigid modulus, which were then substituted into the bubble growth and stability model for numerical simulation. Referring to Considère criterion, it was found that the LLDPE/LDPE blends with a mass ratio of 5/95 possessed the best foamability, and the characteristic relaxation time had a significant effect on the foamability. Batch melt foaming experiments also confirmed the simulation results.